Cadavers, Burials and Infections – a hygienic interpretation of Numbers 19:1-21 against the backdrop of African women in the face of pandemics - Mwandayi Canisius (Pharos Journal of Theology)
In Jewish culture, the marking of tombs was almost a mandatory practice for fear that priests would walk on them and incur ritual impurity. This practice is alluded in Jesus’ condemnation of the Pharisees when he says: “Woe to you! You are like unseen graves over which people unknowingly walk’ (Luke 11:44). The custom itself stems from laws regulating ritual cleanliness in Numbers 19:1-21. Wholly, this chapter contains regulations pertaining touching a dead human body or a human bone or a grave or being in a tent with such a body as well as regulations on how to cleanse a defiled person. Similarly, in African traditional religion, one finds injunctions which regulated contact with corpses and graves. Though in both cases these regulations originally address the spiritual realm aiming to uphold ritual purity, hygienically, such laws when observed resulted in the prevention of infectious communicable diseases. It is in light of this that this article seeks to invite present generations to reconsider the resources that the ancients used to minimize the spread of communicable diseases. Using sociological criticism to analyze Numbers 19:1-21, it is the argument of this article that there are noticeable positive effects on human health that are connected to the observance of regulations enshrined in this text. In the same way, there is also something of positive value on human health behind the prohibitions that African women tell their children in matters relating to the dead. Leveraging on women agency, one observes that being vanguards of culture, African mothers try their best to warn children against tampering with graves, but their advice seems unheeded as the younger generations attending funerals hardly take time to clean themselves after handling coffins and randomly walk or sit on graves especially during burials. As the pandemics continue to take a huge toll on lives in our contemporary times vis-à-vis SDG 3 which aims at ensuring healthy lives and promoting well-being for all, there is serious need for a mentality shift, especially among the younger generations and to pay heed to the wisdom of our mothers. As the world continues to face an unpreceded threat of new pandemics, this article is a wake-up call to seriously rethink where we are possibly going wrong. It is an invitation to reconsider the resources that ancients used to minimize the spread of communicable diseases.